Minimally invasive microbiopsies: a novel sampling method for identifying asymptomatic, potentially infectious carriers of Leishmania donovani. Issue 10 (September 2017) - Kirstein, Oscar David; Abbasi, Ibrahim; Horwitz, Ben Zion; Skrip, Laura; Hailu, Asrat; Jaffe, Charles; Li, Lynlee L.; Prow, Tarl W.; Warburg, Alon
Graphical abstract: Highlights: Microbiopsy devices were designed to assess the infectiousness of asymptomatic Leishmania donovani carriers. The microbiopsy devices sample both skin tissues and blood, as do pool-feeding phlebotomine sand flies. Devices were tested on human volunteers in Ethiopia and proven effective, surpassing the sensitivity of finger-pricks. Abstract: Visceral leishmaniasis (VL) is a potentially lethal, sand fly-borne disease caused by protozoan parasites belonging to the Leishmania donovani species complex. There are several adequate methods for diagnosing VL, but the majority of infected individuals remain asymptomatic, comprising potential parasite reservoirs for transmission of the disease. The gold standard for assessing host infectiousness to biting vector insects is xenodiagnosis (i.e. scoring infection rates among insectary-reared insects that had fed on humans suspected of being infected). However, when it comes to sand flies and leishmaniasis, xenodiagnosis is an intricate operation burdened by logistical hurdles and ethical concerns that prevent its effective application for mass screening of widely dispersed communities, particularly in rural regions of underdeveloped countries. Minimally invasive microbiopsy (MB) devices were designed to penetrate the skin to a depth of ∼200 µm and absorb blood as well as skin cell lysates, mimicking the mode by which phlebotomine sand flies acquire blood meals, as well as their composition. MBs taken from 137 of 262 volunteers, living in endemic VL foci in Ethiopia, detected Leishmania parasites that could potentially be imbibed by feeding sand flies. Although the volume of MBs was 10-fold smaller than finger-prick blood samples, Leishmania DNA detection rates from MBs were significantly higher, implying that skin, more often than blood, was the source of parasites. Volunteers with histories of VL were almost as likely as healthy volunteers to test positive by MBs (southern Ethiopian focus: 95% CI: 0.35–2.59, P  = 1.0. northern Ethiopian focus 0.87: 95% CI: 0.22–3.76, P  = 1), suggesting the importance of asymptomatic patients as reservoirs of L. donovani . Minimally invasive, painless MBs should be considered for reliably and efficiently evaluating both L. donovani infection rates among large numbers of asymptomatic carriers and their infectiousness to blood-feeding sand flies.